Understanding the spectrum of rhino-orbito-cerebral mucormycosis: clinical presentation, management strategies, and prognostic markers in an Indian tertiary care setting - Kishve, Sanjay; Kishve, Prajakta; Reddy, G. Pavan Kalyan (International Journal of Research in Medical Sciences, 2024)
Background: Rhino-orbito-cerebral mucormycosis (ROCM) is an angio-invasive fungal infection characterized by tissue infarction and necrosis. Its incidence has surged, particularly in the backdrop of the ongoing COVID-19 pandemic, necessitating a comprehensive understanding of its clinical presentation, management outcomes, and prognostic factors. Methods: This retrospective cohort study analyzed data from 100 ROCM patients admitted to a tertiary care hospital in India between February 2021 and September 2021. Clinical presentations, laboratory investigations, treatment outcomes, and adverse reactions were assessed. Associations between comorbidities (diabetes mellitus, COVID-19) and mortality were analyzed using odds ratios, and relative risks. Results: The study cohort comprised 55 male and 45 female patients, with a mean age of 52 years. Diabetes mellitus was prevalent in 83% of patients, with 80% testing positive for COVID-19. Common presenting symptoms included ophthalmoplegia (71%) and diminution of vision (58%). Initial investigations revealed a high incidence of paranasal sinusitis and maxillary osteomyelitis. Treatment involved intravenous liposomal Amphotericin-B and aggressive surgical debridement. The mortality rate was 17%, with diabetes mellitus and COVID-19 significantly associated with mortality. Conclusions: ROCM presents substantial morbidity and mortality, particularly among patients with comorbidities such as diabetes mellitus and COVID-19. Early diagnosis, prompt initiation of antifungal therapy, and aggressive surgical intervention are essential for improving patient outcomes. Multidisciplinary collaboration and proactive management strategies are imperative in addressing the challenges posed by this invasive fungal infection.